Pengaruh Brand Awareness dan Harga Terhadap Keputusan Pembelian Tiket Bus DAMRI di Bandara Soekarno - Hatta (Studi pada Penumpang Bus DAMRI Tujuan Kota Bekasi di Bandara Soekarno - Hatta) - Via Siti Fatimah; Syahrul Reza; Dewi Nurbaiti (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This study aims to determine the effect of Brand Awareness and Price on the Decision toPurchase DAMRI Bus tickets at Soekarno - Hatta Airport. This study uses quantitative researchmethods with associative types and with primary data as a source of data obtained from theresults of the questionnaire. The population of this study were passengers and airportemployees who took the DAMRI route from Soekarno Hatta Airport to Bekasi in March whosepopulation is not known with certainty and with a sample of 110 people. The analytical methodused is validity test, reliability test, normality test, analysis of multiple linear regressioncorrelation coefficients, coefficient of determination test, and hypothesis testing using SPSS.The results of this study indicate that: (1) Brand Awareness has a positive effect on PurchaseDecisions with a regression value of 0.538 and a significance level of 0.000 (2) Price has apositive effect on Purchasing Decisions with a regression value of 0.474 and a significance levelof 0.000 (3) Brand Awareness and Price simultaneously has a positive effect on PurchaseDecisions with a calculated F value of 9.056 which is greater than F table of 3.08 and asignificance level of 0.000 less than 0.05 (4) The magnitude of the influence of BrandAwareness and Price on Purchase Decisions is 62.20% while the rest 37.80% is influenced byother variables not examined by the author.